2011
DOI: 10.2139/ssrn.1991148
|View full text |Cite
|
Sign up to set email alerts
|

Educational Achievement of Second Generation Immigrants: An International Comparison

Abstract: This paper investigates the educational achievements of second generation immigrants in several OECD countries in a comparative perspective.We first show that the educational achievement (measured as test scores in PISA achievement tests) of children of immigrants is quite heterogeneous across countries, and strongly related to achievements of the parent generation. The disadvantage considerably reduces, and even disappears for some countries, once we condition on parental background characteristics.Second, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
42
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 25 publications
9
42
0
Order By: Relevance
“…This interpretation is supported by the findings of Dustmann et al (2012) for Turkish second generation immigrants. Another possible interpretation that might play a role is return migration.…”
supporting
confidence: 72%
“…This interpretation is supported by the findings of Dustmann et al (2012) for Turkish second generation immigrants. Another possible interpretation that might play a role is return migration.…”
supporting
confidence: 72%
“…In the context of migrant inclusion, proficiency in the national language has been shown to be a key determinant of educational success for children of immigrants (e.g., Dustmann et al, 2012;Schneeweis, 2011). This study adds to this literature by providing first evidence on an important interaction between migrants' proficiency in the national language and the age of first tracking into different types of secondary schools by ability.…”
Section: Resultsmentioning
confidence: 67%
“…Previous studies already showed that second-generation migrants perform substantially better when they are more proficient in the national language (e.g., Dustmann et al, 2012;Schneeweis, 2011). Moreover, Akresh and Akresh (2010) provide experimental evidence that foreign-born students have better test results when taking a test in their native language instead of the language of the host country.…”
Section: Effect Heterogeneitymentioning
confidence: 89%
“…Studies show that ethnic minority children and those who do not speak the language of instruction as their first language can progress and catch up to their peers in educational performance as they become increasingly proficient in their language (Dustmann et al 2012;De Paola & Brunello 2016;Janta & Harte 2016).…”
Section: %mentioning
confidence: 99%